Anti-Aggregation Function of Blood Vessels in Piglets of Dairy and Plant Nutrition - S. Tkacheva, Elena; N. Medvedev, Ilya (KnE Life Sciences, 2021)
Modern pig farming is a significant sector of modern agriculture in many countries. The attractiveness of its products is associated with their excellent taste and economic affordability. The intensive development of pig breeding considers the latest achievements in the field of pig biology during their early ontogenesis. Optimal functioning of hemostasis in growing piglets relies on platelet activity. Its low severity during the phase of milk and vegetable nutrition provides them with the optimal functional state of primary hemostasis, the success of microcirculation in the internal organs, and sufficient activity of all functional and biochemical processes. In the blood of healthy piglets during the phase of dairy and plant nutrition, a decrease in the number of peroxidation products was noted due to an increase in the level of antioxidant protection of their plasma. This minimized their platelet and vascular wall alteration and provided optimal platelet-vascular interactions. This study shows that the gradual increase in the platelet aggregation that develops in piglets at this age is functionally balanced by the increase in the disaggregation properties of blood vessels and creates conditions for optimal blood flow in small-caliber vessels. Keywords: piglets, phase of dairy and plant nutrition, platelets, aggregation, disaggregation, early ontogenesis